Analysis of Partnership of Private Practice Midwife in The National Health Insurance Program in District Bungo Jambi Province - Azwar, Nurlie; Soewondo, Prastuti (UI Scholars Hub, 2018)
On January 1, 2014, the government began to implement the National Health Insurance (NHI) program to realize social welfare for the whole community. Midwifery and neonatal care in the NHI program involves Puskesmas/family doctors and Private Practice Midwife (PPM) as its network. PPM participation in the NHI program in Bungo District was still lacking, only 12 (54.5%) PPM have cooperated with family doctors from 22 existing PPM. This study aimed to get an overview of PPM participation in the NHI program in Bungo District, Jambi Province. The study used qualitative research approach with Rapid Assessment Prosedur design, purposive sampling, and conducted in-depth interview to 10 PPM, Head of Health Office, MPKP BPJS Health Manager, and Chairman of Bungo Regency Section of Indonesian Midwife Organization (IMO). The study was conducted from January to July 2017. The study found that the knowledge, perceptions and attitude towards NHI program were good, but the perceived toward the claim and predetermined tariff procedures were not so good. PPM motivated to join the NHI program as many patients had become NHI participants. Support from the Government, NHI, and IMO were low, either in the form of socialization, or policies. Therefore, the study suggest an improvement in claims procedures, tariffs, and an increase of socialization from government, NHI and IMO on NHI program related to obstetric and neonatal care.